1973
DOI: 10.1901/jaba.1973.6-57
|View full text |Cite
|
Sign up to set email alerts
|

REDUCING DELUSIONAL SPEECH IN CHRONIC, PARANOID SCHIZOPHRENICS1

Abstract: Four schizophrenic patients with paranoid and grandiose delusions who had been hospitalized for an average of 17 yr were exposed to social reinforcement contingencies in a multiple baseline design. During the baseline period, each patient was interviewed for four 10-min sessions each day. The elapsed time from onset of conversation to onset of delusional talk was recorded. At the end of each day, the patients engaged in a 30-min informal chat with a nurse-therapist while relaxing with coffee, snacks, and cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
0
3

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 10 publications
7
33
0
3
Order By: Relevance
“…This present study extends work (Liberman, Teigen, Patterson, and Baker, 1973) that demonstrated that the duration of rational talk during time-sample interviews increased when the length of a free conversation and snack period was made contingent on the duration of rational talk during daily time-sample interviews. The subject of the present report, Mary N., had shown increased rational talk under these conditions, but continued to answer with 1The interpretation and conclusions in the paper are those of the authors and are not to be construed as official or as necessarily reflecting the policy of the California Department of Mental Hygiene bizarre, incorrect responses when asked direct questions concerning her personal history.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…This present study extends work (Liberman, Teigen, Patterson, and Baker, 1973) that demonstrated that the duration of rational talk during time-sample interviews increased when the length of a free conversation and snack period was made contingent on the duration of rational talk during daily time-sample interviews. The subject of the present report, Mary N., had shown increased rational talk under these conditions, but continued to answer with 1The interpretation and conclusions in the paper are those of the authors and are not to be construed as official or as necessarily reflecting the policy of the California Department of Mental Hygiene bizarre, incorrect responses when asked direct questions concerning her personal history.…”
supporting
confidence: 80%
“…This unit (Liberman, et al, 1973) is a 12-bed token economy ward in which patients are treated with specific behavior modification programs. Mary N. had been living on the unit for 10 months.…”
Section: Subjectmentioning
confidence: 99%
“…One way that researchers have brought the transfer of treatment gains to other settings has been to manipulate antecedent stimuli (Horton, 1975). Furthermore, other investigators have reported greater stimulus generalization to transfer settings as the similarity to the training setting was increased (Liberman, Teigen, Patterson, and Baker, 1973). Many of the stimuli used in the present study in the generalization setting were different from those in the training setting; a different room, materials, experimenter, and observers were used.…”
Section: Refusals To Sharementioning
confidence: 85%
“…The use of praise rather than tangibles such as tokens may have been important. Liberman et al (1973) have noted that "social reinforcement may possibly facilitate generalization because it is the relevant factor in the settings where generalization is tested" (p. 63).…”
Section: Refusals To Sharementioning
confidence: 99%
“…A number of psychologists applied reinforcement techniques to try to reduce the time that patients spoke about delusions (e.g. Wincze et al, 1972;Liberman et al, 1973). However, there has been a remarkable transformation in how delusions are viewed.…”
mentioning
confidence: 99%